PENGARUH AKTIVASI ADSORBEN BIOMASSA TERHADAP GUGUS HIDROKSIL PADA PROSES ADSORPSI ION LOGAM TIMBAL (Pb) - Abdurrahman; Suhendrayatna; Syahiddin DS (Talenta Publisher (Universitas Sumatera Utara), 2016)
Lead (Pb) is a very popular and widely metal known by public caused by high use in industries and toxid to living organisms. This research was conducted to investigate the absorption process of Pb ion in synthetic wastewater. The observations focused on the absorption performance by an adsorbent from mixture biomass of palm bunches and rice husk activated with citric acid in various concentrations and observed an increase in the wave number bonding hydroxyl group (OH) after activated with citric acid. Kinetics of adsorption occured at wave number 3200-3600 cm-1 which founded very good performance of hydroxyl groups in the absorption process in that IR spectra area. Pb ion absorption was found the best place on the ratio of biomass (palm bunches: rice husk) 1: 1, which occured 56.70% absorption with initial concentration of 80 ppm. Furthermore, it was found that contact time between adsorbent and metal ions Pb affect to the absorption.